IDENTITAS DIASPORIS TIGA GENERASI PEREMPUAN CINA DALAM ONLY A GIRL KARYA LIAN GOUW (DIASPORIC IDENTITY OF THREE GENERATIONS OF CHINESE FEMALES IN ONLY A GIRL WRITTEN BY LIAN GOUW) - Asmarani, Ratna (Balai Bahasa Jawa Timur, 2019)
Identity is crucial in a person?s life. Diasporic identity is much more complicated because it involves at least two cultures. The focus of this paper is to analyze the diasporic identity of three generations of diasporic Chinese females as represented in Lian Gouw?s novel entitled Only A Girl. The data and supporting concepts are compiled using library research and close reading. The qualitative analysis is used to support the contextual literary analysis combining the intrinsic aspect focusing on the female characters and the extrinsic aspect concerning diaspora and identity. The results shows that each Chinese female character has tried to construct her own diasporic identity. However, the social, cultural, political, educational, and economic contexts play a great role in the struggles to construct the diasporic identity. It can be concluded that the younger the generation, the braver their effort to construct their diasporic identity and the braver their decision to take a distance with the big family house eventhough they have to face stronger and more complicated conflict to realize and actualize their personal construction of diasporic identity.